2005
DOI: 10.3136/nskkk.52.553
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Whipping Speed on the Physical Characteristics of Whipped Cream

Abstract: For the purpose of investigating the influence of whipping speed on the characteristics of whipped cream, ./ῌ-fat fresh cream was whipped at low speed (+,* or +.* rpm) or high speed (+2* or ,,* rpm). The storage modulus of low-speed whipped cream did not change during storage, but a decrease in storage modulus was observed for high-speed whipped cream. The air bubble size distribution of low-speed whipped cream was stable over time, but that of high-speed whipped cream was found to increase. The reason for thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 6 publications
2
5
0
Order By: Relevance
“…ΔPD decreased as the beating speed decreased. These results were in accordance with the findings of Ihara et al (2005). The correlation was higher than that between whipping time and ΔPD (data not shown), indicating that beating speed itself affected ΔPD.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…ΔPD decreased as the beating speed decreased. These results were in accordance with the findings of Ihara et al (2005). The correlation was higher than that between whipping time and ΔPD (data not shown), indicating that beating speed itself affected ΔPD.…”
Section: Resultssupporting
confidence: 91%
“…The properties of bubble and fat-globule aggregation of the whipped cream might cause this phenomenon. A slow beating speed would result in a narrow distribution of air-bubble size in the cream (Ihara et al, 2005), which might be one of the underlying reasons. Decreasing the beating speed decreased ΔPD but increased the whipping time, which reduced the productivity of making whipped cream.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known empirically that these factors can be controlled by altering the whipping conditions. Ihara et al (2005Ihara et al ( , 2007 studied the influence of whipping speed on the physical characteristics of whipped creams. They showed that creams that are whipped at a lower speed are relatively stable during storage and suggested that the stability of the air bubble surface influences the total stability of whipped creams.…”
Section: Introductionmentioning
confidence: 99%
“…In theory, the differences between a dairy cream and a recombined cream should provide information regarding the characteristics of the emulsifying components in the recombined cream. Demulsification of fat globules is one of most the important factors underlying the firmness of whipped cream (Ihara et al, 2005(Ihara et al, , 2010. Thus, the effects of the emulsifying components on the stability of fat globules were evaluated by measuring their shear stabilities and changes in fat-globule shape.…”
Section: Evaluation Of the Shear Stability Of Dairy Cream And Recombimentioning
confidence: 99%